Efektivitas Manajemen Sekolah Dalam Meningkatkan Standar Mutu Pendidikan Di SMP Negeri 1 Singkohor Aceh Singkil - Supriadi, Agung; Pratiwi, Sri Nurabdiah (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
This research aims to determine "The Effectiveness of School Management in Improving Education Quality Standards at SMP Negeri 1 Singkohor Aceh Singkil. This type of qualitative research uses observation, interview and documentation data collection techniques. Data analysis techniques use data reduction, data presentation and conclusions. The results of the research show School Management Planning in Improving Education Quality Standards at Singkohor State Middle School 1 Aceh Singkil Curriculum development for Singkohor State Middle School 1 includes serving the diversity of students, preparing a curriculum that applies nationally and locally in accordance with local interests, as well as professionally verifying the type of education, provision of adequate learning facilities and infrastructure. Implementation of the program to improve the quality of education through conducting seminars, training, forming a teaching team, participating in MGMP activities, comparative studies, searching for new information through reading and the internet, purchasing supporting books. Secondly, providing infrastructure, namely equipping laboratories and things that support school program activities. Third, student development through reading books and providing counseling guidance. Evaluation of school management in improving education quality standards at SMP Negri 1 Singkohor 1) visiting the library and carrying out reading activities 2) bringing reading materials they like to exchange with their classmates 3) holding discussion activities in retelling stories and pasted on the school wall. The two counseling guidance activities, namely self-monitoring, are one of the supporting strategies for providing information.